Characterizing Soil Morphological Properties at Forest Rehabilitation Sites in Sabal Forest Reserve, Sarawak - Izwaida, Che Adanan; Mohd Effendi, Bin Wasli; Mugunthan, A/L Perumal; Soo, Ying Ho; Mohd Syafiq, S. (2016)
Changes in the forest ecosystem induced by human or other organisms will alter the diversity of the tree species and to certain extend the properties of the soil. For instance, soil compaction and erosion occurred as the result of deforestation activities. Hence, necessary action is needed to recover the degraded land areas affected by these activities by forest rehabilitation. However, forest recovery requires time in order to influence the improvement in terms of soil fertility and productivity. These differences in soil properties which are associated with landscape position are usually attributed to differences in terms of surface runoff, erosion and deposition processes in which, will affect the soil genesis processes (Dengiz 2010). Previous research has reported on the importance of clarifying the soil properties of land area after forest rehabilitation in order to provide information on whether the land has recovered sufficiently over time since its implementation (Arifin et al. 2007). For the case of forest rehabilitation at degraded lands in Sarawak, investigation on the soil properties is essential in order to provide significant information if the soil has recovered after the implementation of forest rehabilitation sites using local tree species. Therefore, the aim of this study was to characterize the soil morphology of the rehabilitated degraded forest land (3 years, 4 years and 31 years after planted with Shorea macrophylla).